2017
DOI: 10.22178/pos.23-7
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Low-Skilled Workers’ Performance in Construction Projects

Abstract: Skilled workers' performance is one of the crucial aspects of labour productivity that requires proper attention for effective projects delivery in the construction industry. The level of skilled workers' low performance has been seen to be a major factor which contributes toward inefficient construction projects productivity. Therefore, the objective of this research is to identify the causes of low-skilled workers' performance in construction projects in the Nigeria. The objective was achieved through a stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…However, highly skilled workers are described by their qualification in higher education from tertiary institutions and the capacity to perform complex tasks, creativeness and adaptableness to technological innovations (ILO, 2014). In the construction industry, the workforce classified as skilled workers have different abilities ranging from apprentices to trades administrator and supervisors (Liepmann as cited in (Zannah et al, 2017). The general skilled workers who do not necessarily require a higher education qualification comprised the bricklayer, carpenter, welder, electrician, tiller, plumber, painter and the likes.…”
Section: The Workforce In the Construction Industrymentioning
confidence: 99%
“…However, highly skilled workers are described by their qualification in higher education from tertiary institutions and the capacity to perform complex tasks, creativeness and adaptableness to technological innovations (ILO, 2014). In the construction industry, the workforce classified as skilled workers have different abilities ranging from apprentices to trades administrator and supervisors (Liepmann as cited in (Zannah et al, 2017). The general skilled workers who do not necessarily require a higher education qualification comprised the bricklayer, carpenter, welder, electrician, tiller, plumber, painter and the likes.…”
Section: The Workforce In the Construction Industrymentioning
confidence: 99%
“…The study further showed how most project challenges occur due to poor health and safety practices. Besides, naive risk analysis and inappropriate identification of project consequences in areas of safety concern were amongst critical challenges constraining project managers from competently performing during mega infrastructure construction (Zannah et al, 2017).…”
Section: Project Complexity In Construction Terminologymentioning
confidence: 99%
“…Though, Zannah, Latiffi, Raji, Waziri and Mohammed (2017) had warned that the process of recruitment into such crafts needs to be carefully thought-out, as for an individual to venture into a particular craft within the construction industry; certain qualities need to be met. They include Physical strength and stamina, manual dexterity and coordination, knowledge and analytical skills, and in-depth knowledge in handling the tools and equipment.…”
Section: Construction Industry and The Increasing Need For Skilled Wo...mentioning
confidence: 99%